How the Psychology of Education Contributes to Research With a Social Impact on the Education of Students With Special Needs: The Case of Successful Educational Actions - Duque, Elena; Gairal, Regina; Molina, Silvia; Roca, Esther (Frontiers in Psychology, 2020)
One current challenge in the psychology of education is identifying the teaching strategies and learning contexts that best contribute to the learning of all students, especially those whose individual characteristics make their learning process more difficult, as is the case for students with special needs. One main theory in the psychology of education is the sociocultural approach to learning, which highlights the key role of interaction in children’s learning. In the case of students with disabilities, this interactive understanding of learning is aligned with a social model of disability, which looks beyond individual students’ limitations or potentialities and focuses on contextual aspects that can enhance their learning experience and results. In recent years, the interactive view of learning based on this theory has led to the development of educational actions, such as interactive groups and dialogic literary gatherings, that have improved the learning results of diverse children, including those with disabilities. The aim of this paper is to analyze the social impact achieved by a line of research that has explored the benefits of such successful educational actions for the education of students with special needs. National and European research projects based on the communicative methodology of research have been conducted. This methodology entails drawing on egalitarian dialogue with the end-users of research—including teachers, students with and without disabilities, students’ relatives and other community members—to allow an intersubjective creation of knowledge that enables a deeper and more accurate understanding of the studied reality and its transformative potential. This line of research first allowed the identification of the benefits of interactive learning environments for students with disabilities educated in mainstream schools; later, it allowed the spreading of these actions to a greater number of mainstream schools; and more recently, it made it possible to transfer these actions to special schools and use these actions to create shared learning spaces between mainstream and special schools. The improvement of the educational opportunities for a greater number and greater diversity of students with special needs evidences the social impact of research based on key contributions of the psychology of education.